Slovesnost ob 20-letnici Pleteršnikovega muzeja v Pišecah in okrogla miza Slovensko slovaropisje (Pišece, 2. 10. 2014) - Jesenšek, Marko; Snoj, Marko; Mirtič, Tanja; Krvina, Domen; Orel, Irena; Ulčnik, Natalija; Karničar, Ludvik; Novak, France; Borovnik, Silvija; Zorko, Zinka (Slavia Centralis, 2020)
The article covers material created during the ceremony marking the 20th anniversary of the Pleteršnik's Museum in Pišece.
Keywords: Maks Pleteršnik; Pišece; round table; Slovenian lexicography; material; Pleteršnik Museum